DETERMINING FACTORS OF INTEREST IN THE USE OF TECHNOLOGY READNESS BASED MULTI LANE FREE FLOW (MLFF) - Arshad Yahya Harnanda; Sigit Priyanto; Muhammad Zudhy Irawan (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
One of the countries with the most vehicle users in the world is Indonesia. The increasing number of vehicle users causes traffic jams, especially in big cities. Toll roads are a solution to get to your destination quickly and avoid traffic jams. One of the smoothness on the toll road is influenced by the service time at the toll gate when making transactions. However, traffic jams at toll gates cannot be avoided due to the long transaction time at toll gates. The plan to implement Multi Lane Free Flow or multi-lane non-stop toll payments is a system that allows toll road users not to need to stop or slow down their vehicles for transactions at toll gates. Socialization and belief in new technology is the current focus. Therefore it is necessary to carry out an analysis of public interest in the implementation of the electronic transaction system that will be implemented, the response of toll road users and the interest of toll users to use contactless Multi Lane Free Flow (MLFF) technology. The method in this research is descriptive analysis to analyze the characteristics of the user towards the contactless system at toll gates based on Multi Lane Free Flow (MLFF) using the Modified UTAUT Model. This study was then analyzed using Moderate Linear Regression using SEM-PLS to find out the factors that influence the interest in using contactless Multi Lane Free Flow (MLFF) with the analysis of the effect of the variables Performance Expectancy, Effort Expectancy, Social Influence, Habit on the use of the new Multi Lane Free technology Flow (MLFF) by adding Technology Readness as a moderating variable using Partial Least Square (PLS). The results of the analysis show that the characteristics of the respondents are related to the interest in using MLFF which can be shown in terms of income, occupation, gender, age, frequency of use of toll roads, segments of toll road use and reasons for using toll roads and the UTAUT Model, namely Performance Expatancy and Social Influence, have an effect on interest in using technology. MLFF except for the Effort Expatancy and Habit variables. Technology Readiness also supports the influence of UTAUT (Performance Expectancy, Effort Expectancy, Social Influence, Habit) on Behavior Intention except that the Performance Expaectancy variable does not depend on Technology Readiness and from the analysis results the use of MLFF is more efficient when used in dense cities like Jabodetabek and less efficient when used in the area is not congested because there is no delay at the toll gate. Keywords: Multi Lane Free Flow , Model UTAUT , Technology Readiness , SEM-PLS